Type I ELM filament heat fluxes on the KSTAR main chamber wall. (August 2017) - Bae, M.-K.; Pitts, R.A.; Bak, J.G.; Hong, S.-H.; Kim, H.S.; Lee, H.H.; Kang, I.J.; Chung, K.-S.
Highlights: To investigate the ELM filamentary phenomena in the far SOL of KSTAR during type I ELMs, poloidal electric probes were used. The far-SOL plasma parameters such as electron temperature, plasma density, heat and particle flux, and radial velocity of ELM to the wall measured by triple probe configuration. The radial velocity is strongly dependent upon the particle flux of filament and separatrix position, while it is weakly depends upon the heat flux. Abstract: Heat loads deposited on the first wall by mitigated Type I ELMs are expected to be the dominant contributor to the total thermal plasma wall load of the International Thermonuclear Experimental Reactor (ITER), particularly in the upper main chamber regions during the baseline H-mode magnetic equilibrium, due to the fast radial convective heat propagation of ELM filaments before complete loss to the divertor. Specific Type I ELMing H-mode discharges have been performed with a lower single null magnetic geometry, where the outboard separatrix position is slowly (∼7 s) scanned over a radial distance of 7 cm, reducing the wall probe–separatrix distance to a minimum of ∼9 cm, and allowing the ELM filament heat loss to the wall to be analyzed as a function of radial propagation distance. A fast reciprocating probe (FRP) head is separately held at fixed position toroidally close and 4.7 cm radially in front of the wall probe. This FRP monitors the ELM ion fluxes, allowing an average filament radial propagation speed, found to be independent of ELM energy, of 80–100 ms −1 to be extracted. Radial dependence of the peak filament wall parallel heat flux is observed to be exponential, with the decay length of λ q, ELM ∼25 ± 4 mm and with the heat flux of q ∥, ELM = 0.05 MWm −2 at the wall, corresponding to q ∥ ∼ 7.5 MWm −2 at the second separatrix. Along with the measured radial propagation speed and the calculated radial profile of the magnetic connection lengths across the SOL, these data could be utilized to analyze filament energy loss model for the future machines.